Do it: The Compendium - Altshuler, Bruce; Fowle, Kate; Giarratano, Frances Wu; Hu Fang; Obrist, Hans Ulrich; Perez-Ratton, Virginia; Presa, Elizabeth (NY; Independent Curators International, 2013)
Curated by Hans Ulrich Obrist, Do It began in Paris in 1993 as a conversation between the artists Christian Boltanski and Bertrand Lavier and Obrist himself, who was experimenting with how exhibition formats could be rendered more flexible and open-ended. The discussion led to the question of whether a show could take (3z(Bscores(3y (Bor written instructions by artists as a point of departure, which could be interpreted anew each time they were enacted. To test the idea, Obrist invited 13 artists to send instructions, which were then translated into nine different languages and circulated internationally as a book. Within two years, Do It exhibitions were being created all over the world by realizing the artists$1 (Binstructions. With every version of the exhibition new instructions were added, so that today more than 300 artists have contributed to the project.s
English
Keywords: Art- Society; Civic engagement; N7560-8266 Visual Arts. Special subjects of art